Penerapan liveworksheets sebagai E-Lkpd untuk menunjang pembelajaran bahasa jerman kelas X IPS 1 di SMA Negeri 1 Lawang - Khoiroh, Alikhatul; Indriwardhani, Sri Prameswari (Fakultas Sastra Universitas Negeri Malang, 2022)
During Covid 19 Pandemic is in SMA Negeri 1 Lawang hybrid learning occurred, and an interactive student task are needed. Liveworksheets is one of the apps that offered, this article explains the process of implementation of Liveworksheets with material sich und andere vorstellen on German class and to describe students' responses about German learning process through the app. Descriptive qualitative research method was used. The Results from two Observers during the Implementation obtained that Liveworksheets runs very well, and the results of the questionnaire filled out by 30 students shows that their response are good.